Menembus Dominasi Patriarki: Strategi Politik Keterpilihan Dilla Hich sebagai Bupati Tanjung Jabung Timur - Putri Aniisah; Mariatul Qibtiyah; Muliono Muliono (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The 2024 simultaneous regional elections reaffirm the persistent underrepresentation of women in local politics, despite a gradual rise in female political participation. Amid the dominance of patriarchal political structures, the victory of Dilla Hich as Regent of Tanjung Jabung Timur emerges as a significant phenomenon that reflects a shift in local electoral dynamics while opening broader opportunities for women’s political representation. This study aims to analyze the political strategies employed by Dilla Hich and examine how her identity and social positioning as a woman contributed to her electoral success. Using a qualitative approach with a case study method, data were collected through in-depth interviews, field observations, and documentation from official sources. The findings indicate that Dilla Hich’s success was not solely rooted in her social capital and extensive political networks but also in the adaptive combination of offensive and defensive political strategies she implemented. Offensive strategies were reflected in the expansion of new voter bases and the strengthening of her personal image, while defensive strategies focused on maintaining loyal supporters and consolidating internal networks. Additionally, the strategic use of gender identity enhanced public acceptance of her leadership. This study concludes that Dilla Hich’s victory demonstrates how structured, inclusive, and adaptive political strategies can challenge patriarchal dominance and create greater opportunities for women in local electoral politics.